1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Derivative Proof

  1. Jan 17, 2009 #1
    1. The problem statement, all variables and given/known data
    if f' is continuous, show that:
    [tex]\mathop{\lim}\limits_{x \to 0}(\frac{f(x+h)-f(x-h)}{2h})=f'(x)[/tex]
    be sure to explain why f' must be continuous

    2. Relevant equations
    not really any equations, this is for AP Calc BC and we've just done L'Hospital's theorem and the derivatives/integrals of logs and inverse trig functions.

    3. The attempt at a solution
    I know that as x-->0 it becomes [tex]\frac{f(h)-f(-h)}{2h}[/tex] . I thought about proving that the difference quotient can be manipulated into the above formula, but haven't had any success.

    Any pointers?
  2. jcsd
  3. Jan 17, 2009 #2


    User Avatar
    Gold Member

    Are you certain that it's supposed to be as x -> 0 and not h? Aside from that, my only suggestion is to add and subtract f(x)/2h and apply some limit lemmas.
  4. Jan 17, 2009 #3
    yeah it says x-->0
    what is a 'limit lemma'? o_O
  5. Jan 17, 2009 #4
    I think jgens is right, it's likely h -> 0.

    Hmmm, I'm surprised this is Calc BC. I think I've seen this problem in Spivak before.

    The trick is to consider the difference quotient and replace h with -h, and then take the limit as h -> 0. Then you should be able to work with the expression given.

    EDIT: Ok, this is a slightly different problem. Hmmm, see if you can make use of the definition of continuity, and the equivalence of the statements lim x -> a f(x) and lim h -> 0 f(a+h).
    Last edited: Jan 17, 2009
  6. Jan 17, 2009 #5


    User Avatar
    Gold Member

    I think this approach may work:

    Derivative of a function: y = f(x) than y - dy = f(x - h), hence dy/dx = lim h -> 0 (f(x) - f(x - h))/h

    Given (f(x + h) - f(x - h))/2h = (f(x +h) - f(x) + f(x) - f(x - h))/2h. Take the limit as h -> 0 and I think that should yield a solution.

    A limit lemma would be lim x-> c kf(x) = klim x -> c f(x) where k is a constant.
  7. Jan 17, 2009 #6
    thanks i'll give that a try--my only question is how do i get it from x-->0 to h-->0?
  8. Jan 19, 2009 #7
    So it turns out my math teacher actually did write the question wrong... it really is h-->0. it's solved with a simple l'hospital. thanks guys
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook